STUDIES OF MALESIAN PANDANACEAE. II. TWO NEW SPECIES OF PANDANUS STICKM. SECT. FUSIFORMA ST. JOHN - BENJAMIN C. STONE (Research Center for Biology, 1968)
Pandanus saint-johnii and P. soboliferus spp. nov. are described and illustrated and placed in sect. Fusiforma It is proposed to include P.(Acrostigma ) biplicatus St.John and P.(Rykia) magnifibrosus St.John in sect Fusiforma also. .